Presentation and Readability Techniques of PjBL-Based Physics Worksheets in Circular Motion Material to Improve Student Collaboration - Dewi, Niken Nila (Universitas Negeri Padang, 2023)
The presentation of a teaching material, one of which is the Student Worksheet (LKPD), can have an impact on students. LKPD presentation affects students' communication skills, where this communication ability becomes the basis for students to understand a learning material. The purpose of this study was to find out how the Project Base Learning (PjBL)-based Physics LKPD presentation technique improves students' communication skills on circular motion material. This type of research is Research andDevelopment (R&D). The instrument used in the research is the LKPD validation sheet. The data collection technique is in the form of LKPD validation results in the form of presentation and communicative techniques. Based on the results of the study, it was found that the results of validation on the presentation technique according to the first validator got a very good score, while according to the second validator, they scored well on typing accuracy and very well on the presentation sequence. According to the first validator, the communicative component was validated, that is, clarity of language scored well and readability of messages and information scored very well. While the second validator, clarity of language with a good score and readability of messages and information with a very good score. The results of the study can be concluded that the quality of this LKPD is in the good and very good category in terms of presentation and communicative techniques, so that this LKPD can be declared feasible to be applied to students with circular motion material.Keywords :LKPD, presentation technique, legibility, circular motion.